Codex Sinaiticus: The Story of the World’s Oldest Bible. By D. C. Parker - Elliott, J. K. (The journal of theological studies, 2011)
The famous biblical manuscript Codex Sinaiticus has seldom been out of the limelight since Constantine Tischendorf secured parts of it for scholarship towards the end of the nineteenth century. Most of its surviving leaves were acquired by the British Museum in 1933 and these have been exhibited to the general public ever since. To coincide with another momentous milestone in this codex’s history, the digitization of the entire manuscript (the London leaves as well as pages in Leipzig, St Petersburg, and St Catherine’s Monastery, Mount Sinai), the British Library in association with the other participating institutions asked D. C. Parker to write a book about the manuscript, its importance and history.